2021
DOI: 10.21037/gs-20-916
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative and short-term oncological outcomes following laparoscopic versus open pancreaticoduodenectomy after learning curve in the past 10 years: a systematic review and meta-analysis

Abstract: Background: To compare perioperative and short-term oncologic outcomes of laparoscopic pancreaticoduodenectomy (LPD) to open pancreaticoduodenectomy (OPD) using data from large-scale retrospective cohorts and randomized controlled trials (RCTs) in the last 10 years.Methods: A meta-analysis to assess the safety and feasibility of LDP and OPD registered with PROSPERO: (CRD42020218080) was performed according to the PRISMA guidelines. Studies comparing LPD with OPD published between January 2010 and October 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…dissections. Similar radical effects can be considered between RDP and LDP, which is consistent with major existing clinical studies (7,22,24,25,29,38). Meanwhile, this study shows that no significant difference was observed in reoperation, blood transfusion, readmission, overall complication rates, POPF, and major complications (Clavien-Dindo≥3/4 grade) between the RDP group and LDP group, showing that RDP is as safe as LPD after the learning curve.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…dissections. Similar radical effects can be considered between RDP and LDP, which is consistent with major existing clinical studies (7,22,24,25,29,38). Meanwhile, this study shows that no significant difference was observed in reoperation, blood transfusion, readmission, overall complication rates, POPF, and major complications (Clavien-Dindo≥3/4 grade) between the RDP group and LDP group, showing that RDP is as safe as LPD after the learning curve.…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have shown that the operative time and length of hospital stay were the same between RDP and LDP, as most clinical trials have shown ( 22 , 24 , 26 ). Distal pancreatectomy with negative margin and lymph node dissection are two important prognosis factors ( 7 , 22 , 38 ). Based on the tumor radical effect, our study showed that there was no difference in RDP and LDP lymph node dissections.…”
Section: Discussionmentioning
confidence: 99%
“…[8] In 1994, Gagner and Pomp performed the first laparoscopic pancreaticoduodenectomies and opened the way for the development of laparoscopic technology in this field. [9–11] However, the postoperative recovery of the patients was unsatisfactory. [9–11] Due to the surgical complexity and the high rate of postoperative complications, the clinical development of LPD has been questioned, and its clinical application has been halted.…”
Section: Introductionmentioning
confidence: 99%
“…[9–11] However, the postoperative recovery of the patients was unsatisfactory. [9–11] Due to the surgical complexity and the high rate of postoperative complications, the clinical development of LPD has been questioned, and its clinical application has been halted.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, pancreatic surgery was regarded as a dangerous procedure associated with high morbidity and mortality rates. However, advances in surgical techniques and perioperative care, combined with minimally invasive surgery, have resulted in improved postoperative outcomes and enhanced recovery after Diabetes Metab J 2023;47:703-714 https://e-dmj.org pancreatic resection [2,3]. With the introduction of effective chemotherapy regimens, survival outcomes after pancreatectomy have also been improving in patients with pancreatic cancer [4][5][6].…”
Section: Introductionmentioning
confidence: 99%